Envirodevonomics: A Research Agenda for an Emerging Field - Greenstone, Michael; Jack, B. Kelsey (Journal of Economic Literature, 2015)
Environmental quality in many developing countries is poor and generates substantial health and productivity costs. However, the few existing measures of marginal willingness to pay (MWTP) for environmental quality improvements indicate low valuations by affected households. This paper argues that this seeming paradox is the central puzzle at the intersection of environmental and development economics: Given poor environmental quality and high health burdens in developing countries, why is MWTP seemingly so low? We develop a conceptual framework for understanding this puzzle and propose four potential explanations for why environmental quality is so poor: (1) due to low income levels, individuals value increases in income more than marginal improvements in environmental quality; (2) the marginal costs of environmental quality improvements are high; (3) political economy factors undermine efficient policymaking; and (4) market failures such as weak property rights and missing capital markets distort MWTP for environmental quality. We review the literature on each explanation and discuss how the framework applies to climate change, which is perhaps the most important issue at the intersection of environment and development economics. The paper concludes with a list of promising and unanswered research questions for the emerging sub-field of “envirodevonomics.” (JEL I15, O10, O44, Q50)